Left ventricular non-compaction in a patient with Shone's complex - Mehrnoush Toufan; Lelll Pourafkari; Aidin Baghbani - Oskouei; Nader D Nader (KARE Publishing, 2019)
Shone's complex is a rare congenital cardiac malformation characterized by serial obstructive lesions of the left heart at multiple levels. Presently described is an unusual case of an adult male patient who presented with palpitations and worsening dyspnea. An echocardiographic evaluation revealed Shone's complex associated with left ventricular non-compaction cardiomyopathy (NCC). To our knowledge, an association between NCC and Shone's complex has not been previously described.